PENGEMBANGAN APLIKASI INFORMASI KULINER YOGYAKARTA MENGGUNAKAN METODE LOCATION BASED SERVICE - Devie, Erviana; Winarno, Edy (Information Technology and Telematics, 2018)
Abstark Culinary variety in each region is one of the characteristics that can influence the attractiveness of tourists to visit the area. Yogyakarta is one of the world's tourist destinations. In this study a culinary application was made by using a location based service method to get a location point on the application, an application designed to make it easier for users to visit various types of culinary when visiting Yogyakarta by displaying the estimated distance from the user's initial position to the destination. This study utilizes a global positioning system on android devices. In this design haversine formula is used to calculate the user's mileage from the initial position to the destination location. The results of the tests carried out on one data show the difference from the distance of ± 40km.